Growth expectations and banking system fragility in developing economies - Eugenio Proto (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
The likelihood of a banking crisis appears to be higher in fast-developing countries.An explanation is provided in a Diamond and Dybvig framework, where banks are vehicles of consumption-smoothing, offering insurance against shocks to the consumption path of consumers.The theoretical model shows that the higher consumer growth expectations, the higher the optimal level of illiquidity insurance even if it implies higher exposure bank runs.Empirical evidence supports this result and suggests that the effect of deposit interest rates on the probability of crisis is stronger after a period of high, uniterrupted growth.Policies of providing bail-outs or deposit insurance are demonstrated to be efficient even when they increase the fragility of the banking system
URN:NBN:fi:bof-201408072064
Keywords: 330